Generation of a homozygous and a heterozygous SNCA gene knockout human-induced pluripotent stem cell line by CRISPR/Cas9 mediated allele-specific tuning of SNCA expression - Schneider, Yanni; Turan, Soeren; Koller, Aron; Krumbiegel, Mandy; Farrell, Michaela; Plotz, Sonja; Winkler, Jürgen; Xiang, Wei (Stem Cell Research, 2022)
Aggregation of alpha-synuclein (aSyn) is closely linked to Parkinson's disease, probably due to the loss of physiological functions and/or gain of toxic functions of aggregated aSyn. Significant efforts have been made elucidating the physiological structure and function of aSyn, however, with limited success thus far in human -derived cells, partly because of restricted resources. Here, we developed two human-induced pluripotent stem cell lines using CRISPR/Cas9-mediated allele-specific frame-shift deletion of the aSyn encoding gene SNCA, resulting in homo-and heterozygous SNCA knockout. The generated cell lines are promising cellular tools for studying aSyn dosage-dependent functions and structural alterations in human neural cells.
CRIS-Team WoS Importer:2022-11-18